On conditions of technical stability of controlled processes with distributed parameters - Matviichuk, K. S. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We formulate sufficient conditions for the technical stability on given bounded and infinite time intervals and for the asymptotic technical stability of continuously controlled linear dynamical processes with distributed parameters. By using the comparison method and the method of Lagrange multipliers in combination with the Lyapunov direct method, we obtain criteria which define a set of controls providing the technical stability of the output process. We select the optimal control that realizes the least value of the norm corresponding to a given process.